2018
DOI: 10.1038/s41598-018-26084-2
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of Sedum sarmentosum Bunge extract on Tilapia fatty liver via the PPAR and P53 signaling pathway

Abstract: Fatty liver disease is a growing problem in fish aquaculture and there is an urgent need to identify causes and possible remedies. In the present study, the effects of treating fatty liver disease in the Nile tilapia (Oreochromis niloticus Linnaeus, 1758) with an extract derived from a herb, Sedum sarmentosum Bunge (SSB), was investigated. We found that the SSB extract could restore the changes to feed coefficient, immune capacity, and pathological index caused by fatty liver disease, and also prevent apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Previous studies have found that SS prevents D-GalN/LPS-induced fulminant hepatic failure, and this protection is likely associated with SS' anti-apoptotic activity and the downregulation of mitogen-activated protein kinase activity associated at least in part with the suppressed transcription of LPS receptors [6]. SSB extract ameliorates tilapia fatty liver via PPAR and P53 signaling pathways [3]. In the current study, we hypothesized that miR-124 regulates the occurrence and development of D-GalN/LPSinduced acute liver injury by regulating the Hedgehog signaling pathway.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous studies have found that SS prevents D-GalN/LPS-induced fulminant hepatic failure, and this protection is likely associated with SS' anti-apoptotic activity and the downregulation of mitogen-activated protein kinase activity associated at least in part with the suppressed transcription of LPS receptors [6]. SSB extract ameliorates tilapia fatty liver via PPAR and P53 signaling pathways [3]. In the current study, we hypothesized that miR-124 regulates the occurrence and development of D-GalN/LPSinduced acute liver injury by regulating the Hedgehog signaling pathway.…”
Section: Introductionmentioning
confidence: 94%
“…Many active ingredients in traditional Chinese medicine protect the liver from toxic injury and reduce liver tissue damage and the degree of such damage. These active ingredients include polyphenolic compounds, flavonoids, saponin compounds, organic acid compounds, terpenoids, phenylpropanoids, sugars, and alkaloids [3]. Sedum sarmentosum Bunge (SSB), also known as Sedum sarmentosum (SS), has extracts that exert preventive and protective effects on alcohol-induced liver injury [3], but the mechanism remains unclear, and further research is required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grass carp is one of the most important freshwater species in China that can consume artificial diets and water plants (Du et al 2006;Kong et al 2017b). Feeding carp a high-fat diet may lead to fatty liver disease in this species and adversely influence aquaculture production of grass carp (Huang et al 2018). The literature clearly shows that dietary lipids can bring protein sparing effect and enhance growth.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Du et al (2005) showed a positive effect only when dietary lipids were below 4% and a negative effect was observed when dietary lipids were higher than 6% in the growth of grass carp. Furthermore, consumption of a high-fat diet may lead to unwanted hepatic fat deposition (Li et al 2016;Wang et al 2015), dyslipidemia (Sabzi et al 2017;Zhang et al 2018), affect the antioxidative system (Chen et al 2016;Huang et al 2018;Ma et al 2018), and affect normal gut microbiota leading to dysbiosis (Al-Muzafar and Amin 2017; Falcinelli et al 2017;Tian et al 2016). The above-mentioned Hui Zhao and Yan'er Luo contributed equally.…”
Section: Introductionmentioning
confidence: 99%